Use of Filter and Addition of Aeration on Growth of Red Tilapia (Oreochromis niloticus) - Djaelani, Muhammad Anwar; Kasiyati, Kasiyati; Sunarno, Sunarno (Jurnal Veteriner, 2023)
This study wants to prove that the combination of using a filter and adding an aerator will get better results when compared to using only an aerator for the growth of red tilapia (Oreochromis niloticus). Factorial Completely Randomized Design (CRD) with two factors and two levels were used, there were consisting of unfiltered and filtered factors and two levels of aerators, one aerator and two aerators. Fish are kept in containers with a capacity of 150 liters of water with a volume of 120 liters of water. Red tilapia weighing 12±0.9 g was reared for 30 days. The variables observed were fish length, height, weight of fish, carcass weight and protein content of fish meat. Environmental factors observed included dissolved oxygen (DO), pH, temperature, ammonia, nitrite and nitrate content. Data analysis was carried out using analysis of variance (ANOVA) carried out using SPSS. Significant differences between treatments were tested by using the Least Significant Difference test (LSD). There is a significant differences for the each parameter (P<0,05) These results indicate that the use of a filter combined with the addition of an aerator increases the supply of dissolved oxygen which can improve water quality thereby increasing the growth and protein content of red tilapia. It can be concluded that the use of a filter combined with the addition of an aerator can be used as an alternative to improve water quality which has a positive impact on red tilapia productivity.